2001
DOI: 10.1093/rheumatology/40.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-induced remission in rheumatoid arthritis patients is characterized by a reduction in macrophage content of synovial biopsies

Abstract: Remission in RA patients is characterized by a predominant reduction in macrophage content of the synovial membrane, suggesting that current DMARDs may target this cell and its inflammatory mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 8 publications
5
40
0
Order By: Relevance
“…Consistent with the findings in the present study is the clinical experience that patients may start to feel better very early after initiation of infliximab treatment (4). The statistically significant decrease in macrophage numbers is of interest in light of the earlier studies showing an association between the number of synovial tissue macrophages and clinical signs of disease activity (33)(34)(35). After 1 month, the most pronounced reduction of macrophage numbers was found in the patients with clinical improvement.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the findings in the present study is the clinical experience that patients may start to feel better very early after initiation of infliximab treatment (4). The statistically significant decrease in macrophage numbers is of interest in light of the earlier studies showing an association between the number of synovial tissue macrophages and clinical signs of disease activity (33)(34)(35). After 1 month, the most pronounced reduction of macrophage numbers was found in the patients with clinical improvement.…”
Section: Discussionsupporting
confidence: 90%
“…115 A significant reduction in macrophages in the synovial sublining region following treatment with disease-modifying antirheumatic drugs (DMARDs), mostly methotrexate and gold, was demonstrated in another study. 116 This was particularly pronounced in those who were responding clinically by ACR criteria. Although a significant reduction in memory T cells was observed, (and this was interestingly associated with CRP reduction), memory T-cells could still be found in the synovium of patients who attained remission.…”
Section: Cellular Compositionmentioning
confidence: 99%
“…There is evidence of heterogeneity in RA synovial macrophages, as judged by marker expression (146)(147)(148)(149). One interpretation of the biopsy findings mentioned above (145) is that, as proposed earlier, intimal macrophages are long-lived and possibly derive from the more transient sublining population. However, it is also possible that they are independent of each other.…”
Section: Macrophage Lineage Heterogeneitymentioning
confidence: 72%
“…Interestingly, one long-term study, in which RA patients were followed up through remission and the macrophage content of synovial biopsy specimens was observed over time, showed that DMARDs reduced the numbers of both sublining and intimal macrophages (145). There is evidence of heterogeneity in RA synovial macrophages, as judged by marker expression (146)(147)(148)(149).…”
Section: Macrophage Lineage Heterogeneitymentioning
confidence: 99%